AD, Volume 22, n° 3 & 4, 1997 - Full Issue - Journal System (Africa Development, 1997)
Contents Introduction Ibrahim Abdullah. . . . . . . . . . . . . . . . 5 Subaltem Reactions: Lumpen, Students, and the Left Ishmail Rashid ................................ 19 Bush Path to Destruction: The Origin and Character of the Revolutionary United Front (RUF/SL) Ibrahim Abdullah. . . . . . . . . . . . . . . . . 45 The Kemajoi Militia: Violence, Internai Displacementand the Politics of Counter-Insurgency Patritk Muana. . . . . . . . . . . . . . . . . . 77 War and Transition to Peace : A Study of State Conspiracy in Perpetuating Armed Conflict ArthurAbraham................................. 101 Understanding the Politicaland Cultural Dynamicsof the Sierra LeoneWar : A Critique of Paul Richards's Fighting for the Rain Forest Yusuf Bangura................................. 117 The May 25 Coup d'Etat in Sierra Leone: A Militariat Revoit? Lansana Gberie................................. 149 Lumpen Youth Culture and Political Violence: Sierra Leoneans Debate the RUF and the Civil War I. Abdullah, Y. Bangura, C. Blake, L. Gberie, L. Johnson, K. Kallon, S. Kemokai, P. K. Muana, I. Rashid & A. Zack-Williams. . . . 171 Reflections on the Abidjan Peace Accord Yusuf Bangura ................................. 217 Appendices I.Peace Agreement Between the Govemment of Sierra Leone and the Revolutionaty United Front of Sierra Leone (RUF/SL) . . . 243 Il. Economie Community of West Africa States: Sixth Meeting of Foreign Affairs Ministers of the Committee of Five on Sierra Leone . . . . . 253 III. ECOWAS Six-Month Peace Plan for Sierra Leone . . . . . . . . . . . . . . 255 Publications Received and Acquired....................... 259